2022
DOI: 10.1038/s41467-022-27961-1
|View full text |Cite
|
Sign up to set email alerts
|

On-surface synthesis and characterization of nitrogen-substituted undecacenes

Abstract: Heteroatom substitution in acenes allows tailoring of their remarkable electronic properties, expected to include spin-polarization and magnetism for larger members of the acene family. Here, we present a strategy for the on-surface synthesis of three undecacene analogs substituted with four nitrogen atoms on an Au(111) substrate, by employing specifically designed diethano-bridged precursors. A similarly designed precursor is used to synthesize the pristine undecacene molecule. By comparing experimental featu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 82 publications
1
40
0
Order By: Relevance
“…[37] We tentatively attribute such adsorption geometry to the hydrogenation of the nitrogen atoms from pyrazine rings (cf. scheme in Figure 2a), which gives rise to steric hindrance between adjacent tetraazapentacene units, as previously observed for other N-containing acenes [23] and as illustrated in Figure S6 (Supporting Information) by DFT calculations of freestanding P2 with and without extra hydrogenation. Notably, such extra hydrogenation is taking place in the majority of the units, with some exceptions where the tetraazapentacene monomers adopt a more planar configuration allowing to discern the nature of the pyrrolopyrrole bridge (like the example shown in Figure 2e,f).…”
Section: Au(111) Surfacesupporting
confidence: 71%
See 2 more Smart Citations
“…[37] We tentatively attribute such adsorption geometry to the hydrogenation of the nitrogen atoms from pyrazine rings (cf. scheme in Figure 2a), which gives rise to steric hindrance between adjacent tetraazapentacene units, as previously observed for other N-containing acenes [23] and as illustrated in Figure S6 (Supporting Information) by DFT calculations of freestanding P2 with and without extra hydrogenation. Notably, such extra hydrogenation is taking place in the majority of the units, with some exceptions where the tetraazapentacene monomers adopt a more planar configuration allowing to discern the nature of the pyrrolopyrrole bridge (like the example shown in Figure 2e,f).…”
Section: Au(111) Surfacesupporting
confidence: 71%
“…[18][19][20] In particular, in the case of N-containing acenes, so called azaacenes or N-heteroacenes, it has been demonstrated that N-doping is an efficient strategy to engineer their electronic bandgap and/or to induce an open-shell character in their ground state. [21][22][23] Contemporarily to the progress made in the synthesis of 𝜋-conjugated systems on surfaces, the fabrication of low dimensional coordinative metal-organic nanoarchitectures based on metal ions and 𝜋-conjugated ligands has been extensively explored. [24][25][26][27][28] Herein, the on-surface chemistry toolbox of 𝜋-d systems, achieved by direct deposition of molecular ligands that coordinate with substrate adatoms or by codeposition of different metals and ligands, leading to the hybridization of the d-orbitals of transition metals and frontier orbitals of conjugated ligands, has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key intermediate 1 was synthesized at gram-scale quantities according to previously reported procedures. [45] N-7BCOD was obtained in two steps by reacting compound 1 with ethylenediamine and followed by oxidation using 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) to afford a yield of 48 %. In contrast, subjecting compound 1 to dehydration condensation with ophenylenediamine directly generated N-9BCOD at 58 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, methods employing on-surface chemistry under ultrahigh vacuum (UHV) conditions have emerged as powerful techniques that facilitate the synthesis of novel organic materials that are unstable in the solution-state. [12,13,41,45,57,58] This technique may reveal the singlemolecule structure and physical properties of compounds. Furthermore, this method provides an understanding to the reaction mechanism of deposited molecules and the catalytic effect of different metal substrates on the transient structural characteristics of the intermediates.…”
Section: Introductionmentioning
confidence: 99%